2020
DOI: 10.36941/ajis-2020-0066
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Financial Market Integration in Vietnam: A Price – Based Approach

Abstract: This paper investigates the existence of financial market integration between Vietnam and the region (ASEAN, ASIAN) as well as the world using price-based indicators. Our paper is the first to assess the overall integration of the Vietnam financial market based on two different datasets for different sub-capital markets, the bond market and stock market, during the period of 2009 - 2018. The empirical results show that Vietnam, compared to other countries in research, holds lower regional and international int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Finance freedom has accompanied trade and investment integration. Anh et al (2020) demonstrate considerably strong signs of progressing regional and global stock market integration during the period 2009-2018. Vietnam's score for financial freedom experienced a gradual increase from 30 between 1995and 2015, to 40 between 2016, and further to 50 points between 2020(Heritage Foundation, 2023.…”
Section: Economic Liberalizationmentioning
confidence: 99%
“…Finance freedom has accompanied trade and investment integration. Anh et al (2020) demonstrate considerably strong signs of progressing regional and global stock market integration during the period 2009-2018. Vietnam's score for financial freedom experienced a gradual increase from 30 between 1995and 2015, to 40 between 2016, and further to 50 points between 2020(Heritage Foundation, 2023.…”
Section: Economic Liberalizationmentioning
confidence: 99%
“…On the other hand, several studies about ASEAN-5, East Asia and other countries had been done. [4] stated that Vietnam, compared to other countries in research, holds lower regional and international integration levels in both the bond market and the stock market, but demonstrates considerably strong signs of progressing regional and global stock market integration over the period. On the other hand, [15] found that there is cointegration among stock markets while Japan and Singapore appear to provide regional leadership, as they both exert the most significant influence on the other Asian financial markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research considers East and Southeast Asia into two different blocks for the first step, following [5]. We use Japan's stock market index as a benchmark for the region of Asia and East Asia following the study of [5], [4], [5], [15], [16] and use Indonesia as benchmark for the region of Southeast Asia following [5]. We also use East's market and Southeast Asia's market as individual entity to find the short-run causal linkage.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations